أثر تقنيات المونتاج الحديثة على جودة الإنتاج التلفزيوني (Comprehensive Journal of Science, 2025)
Abstract: This research deals with the impact of modern editing techniques on the quality of television production, focusing on the role of color correction and visual effects (VFX) in enhancing the level of visual and audio content. The research reviews the development of editing from traditional methods to modern digital methods, and shows how advanced technologies have contributed to improving the efficiency of television work, both in terms of speed and accuracy. The impact of techniques such as color correction and visual effects on improving image quality and achieving visual and audio effects that attract viewers was also analyzed. In the end, the research concludes that the use of modern techniques in editing has a significant positive impact on the quality of television production, which contributes to the presentation of more professional and attractive works.
Keywords: Keywords: television editing, modern techniques, color correction, visual effects, VFX, visual quality, television production.